Bilateral Thalamic Stroke in a Young Adult: A Rare Presentation of Artery of Percheron Infarction (London Journal of Medical and Health Research, 2025)
Artery of Percheron (AOP) infarcts are rare ischemic strokes resulting from occlusion of a solitary arterial variant supplying the paramedian thalami and rostral midbrain. We present the case of a 26-year-old previously healthy female who presented with acute altered consciousness and vertical gaze palsy. MRI brain revealed symmetric bilateral thalamic diffusion restriction, consistent with AOP infarction. This case underscores the importance of considering this rare stroke subtype in young patients presenting with unexplained coma or altered mental status.
Keywords: macular hole; microinvasive vitrectomy; platelet-rich plasma; internal limiting membrane; Artery of Percheron; thalamic infarct; bilateral stroke; young adult; vertical gaze palsy; altered consciousness